Development of distal metaepiphysis of the femur in conditions of temporary bilateral blocking of the growth zone (experimental study) - Khmyzov, Sergey; Rokutov, Victor; Iershov, Dmytro (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
The use of minimally invasive methods of blocking the long bones growth zone to eliminate the difference in the length of the lower extremities in children is a modern and promising direction. The technique of temporary bilateral blocking of growth zone with screw plates has potential advantages, however, the formation of secondary frontal deformations remains an insufficiently studied issue. Objective: to evaluate the formation of the distal metaepiphysis of the femur in conditions of temporary bilateral blocking of growth zone with plates of different types. Methods: temporary bilateral blocking of the distal growth zone of the right femur is performed in 10 white rabbits at the age of 8 weeks and weighing (1.8 ± 0.2) kg. Animals were divided into groups: 1 (5 rabbits) — non-blocking plates were used, 2 (5) — blocked. An overview radiograph of the lower extremities of the animals was performed immediately after the operation after 3, 5 and 7 weeks. The radiographs were evaluated according to the Paley protocol, mLDFA, PSA, DSA, distance between the «wires-growth zone» in three zones (medial, middle and lateral) were determined. Results: the inhibition of longitudinal growth of growth zone was revealed when both types of plates were used. There were no differences in the angular parameters of the distal femur (mLDFA) between the groups. In group 1, the PSA and DSA values increased significantly during the growth process (p < 0.05), in group 2 — remained unchanged for the entire follow-up period. A significant increase in the «spine-growth zone» distance on the limb in question was noted in group 1 rabbits in the middle zone in dynamics. Conclusions: temporary bilateral blocking growth zone using both types of plates with screws leads to inhibition of its longitudinal growth. During blocking, there were no secondary deformations of the distal metaepiphysis of the femur. Slight growth of the distal growth zone, especially in the middle zone, indicates a residual growth in temporary bilateral blocking conditions with non-blocking plates.